2021
DOI: 10.3390/fluids6070255
|View full text |Cite
|
Sign up to set email alerts
|

Towards Reconstruction of Complex Flow Fields Using Unit Flows

Abstract: Many complex turbulent flows in nature and engineering can be qualitatively regarded as being constituted of multiple simpler unit flows. The objective of this work is to characterize the coherent structures in such complex flows as a combination of constituent unitary flow structures for the purpose of reduced-order representation. While turbulence is clearly a non-linear phenomenon, we aim to establish the degree to which the optimally weighted superposition of unitary flow structures can represent the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Year Frequency Jet Type Study Type (Hz) Kercher et al [6] 2003 1-1000 synthetic Travnicek and Tesar [8] 2003 106-692 synthetic smoke Smith and Swift [1] 2003 synthetic and Schlieren continuous Pavlova et al [9] 2006 420-1200 synthetic Arik [10] 2008 4500 synthetic Chaudhari et al [11] 2009 100-350 synthetic Bazdidi-Tehrani et al [12] 2011 16-400 synthetic Biden et al [13] 2012 unforced jet POD in crossflow Biden et al [14] 2012 forced jet POD in crossflow Ghaffari et al [15] 2016 20,000 ultrasonic microblower Ghadi et al [16] 2016 pulsed smoke impinging jet Albright and Solovitz [17] 2016 variable-diameter synthetic jet Firdaus et al [18] 2018 300-700 synthetic Solovitz et al [19] 2018 350-2000 synthetic PIV Viggiano et al [20] 2018 variable-density POD and PIV jet Kristo et al [21] 2021 crossflow jets POD and PIV Present work 2021 20-100 synthetic POD, smoke, Schlieren Pavlova et al [9] found that high-frequency jets removed heat more effectively, but that lower-frequency jets were better for larger separation distances. Many authors found that the optimal frequency for heat transfer was the resonance frequency for the device or the diaphragm [11,18,19].…”
Section: Citationmentioning
confidence: 99%
“…Year Frequency Jet Type Study Type (Hz) Kercher et al [6] 2003 1-1000 synthetic Travnicek and Tesar [8] 2003 106-692 synthetic smoke Smith and Swift [1] 2003 synthetic and Schlieren continuous Pavlova et al [9] 2006 420-1200 synthetic Arik [10] 2008 4500 synthetic Chaudhari et al [11] 2009 100-350 synthetic Bazdidi-Tehrani et al [12] 2011 16-400 synthetic Biden et al [13] 2012 unforced jet POD in crossflow Biden et al [14] 2012 forced jet POD in crossflow Ghaffari et al [15] 2016 20,000 ultrasonic microblower Ghadi et al [16] 2016 pulsed smoke impinging jet Albright and Solovitz [17] 2016 variable-diameter synthetic jet Firdaus et al [18] 2018 300-700 synthetic Solovitz et al [19] 2018 350-2000 synthetic PIV Viggiano et al [20] 2018 variable-density POD and PIV jet Kristo et al [21] 2021 crossflow jets POD and PIV Present work 2021 20-100 synthetic POD, smoke, Schlieren Pavlova et al [9] found that high-frequency jets removed heat more effectively, but that lower-frequency jets were better for larger separation distances. Many authors found that the optimal frequency for heat transfer was the resonance frequency for the device or the diaphragm [11,18,19].…”
Section: Citationmentioning
confidence: 99%